Employment of Adolescents and Children in the Aspect of Polish Educational Reform – Chosen Legal Problems - Kloczkowska, Milena Jolanta (Review of European and Comparative Law, 2021)
The employment of adolescents is an extremely important phenomenon, although doctrine rarely discusses it. This solution enables young people to gain qualifications early and promises long and successful cooperation for the employer. It should be remembered, however, that at such a young age the most important sphere of life is not work, but education and appropriate psycho-physical development. Bearing in mind the delicacy of children and adolescents, it is necessary to create legal constructions which will protect young people from too early collision with problems connected with work such as: stress, exhaustion, and pressure. The notion of adolescence is constantly intertwined with the notion of child and it is not easy to judge when these terms are used. This article intends to discuss these terms, and to present them through the applicable laws. In addition, the article presents research on the employment of adolescents and children in Poland based on reports from the National Labour Inspectorate. The legislator had a difficult task - to create appropriate regulations which would not only make work possible, but at the same time properly secure the already mentioned most important spheres of life of adolescents and children. This task undoubtedly becomes even more difficult when the change of other legal acts forces a rush to regulate such a delicate legal sphere. The aim of this article is to present advantages and disadvantages of current legal constructions based on the analysis of regulations and statistics.